Discontinuous finite element method for transient conductive heat transfer in layered media with thermal contact resistance. (November 2022) - Wang, Cun-Hai; Zhang, Xiao-Yang; Jiang, Ze-Yi
Abstract: Research on accurately solving the transient conductive heat transfer problem in layered media has both scientific and engineering significance. Numerical algorithms up to date usually suffer from additional dubious treatments when dealing with the temperature discontinuity induced by the thermal contact resistance (TCR) between the inner interface. In this paper, we extend the discontinuous finite element method (DFEM) to solve the problem of transient conductive heat transfer in a layered slab with TCR interfaces. The correctness of the DFEM for handling the TCR-induced temperature discontinuity is verified at first. Then we utilize the DFEM to solve the transient conductive heat transfer problem in a three-layered medium subjected to Dirichlet, Neumann, and Robin boundary conditions, respectively. The time-dependent temperature along the slab and the temperature discontinuity across the TCR interfaces are captured and analyzed. Results indicate the present DFEM can naturally capture the TCR interface-induced temperature discontinuities accurately. The time-dependent temperature and temperature discontinuities across the TCR interfaces presented in this work can serve as benchmarks for later research on conductive heat transfer in layered media. Highlights: DFEM is developed for transient conductive heat transfer in layered media with TCR interfaces. DFEM can naturally capture the TCR interface-induced temperature discontinuity. Transient conductive heat transfer in a three-layered medium with two TCR interfaces is solved. The TCR effects are analyzed for the medium subjected to Dirichlet, Neumann, and Robin boundary conditions.